Poststreptococcal glomerulonephritis with atypical hemolytic uremic syndrome: An unusual presentation - Mital Parekh; Abhijit Konnur; Sishir Gang (Saudi Journal of Kidney Diseases and Transplantation, 2018)
A 14-year-old female presented with oliguric dialysis requiring kidney injury due to acute poststreptococcal glomerulonephritis (PSGN) with hypertension strongly suggestive of atypical hemolytic uremic syndrome (aHUS) with microangiopathic hemolytic anemia and elevated factor H antibody levels. Renal biopsy revealed crescentic glomerulonephritis with typical subepithelial, intramembranous and mesangial electron-dense deposits (humps) on electron microscopy. She was treated with glucocorticoids following which she recovered, remained dialysis free and her Factor H antibody levels and depressed complement 3 levels normalized. PSGN-associated HUS has rarely been described, with this patient being the 11th case reported, to the best of our knowledge. This case is unique as we describe the course and management of the first patient with PSGN-associated HUS in the era of eculizumab, without eculizumab, and plasmapheresis. This patient presented with clinical and histological features of PSGN as well as anemia and thrombocytopenia consistent with aHUS. Given that these diseases are both mediated through the alternate complement pathway, it is tempting to speculate that blockade of the terminal complement pathway through the use of eculizumab might improve outcomes. Temporally, the hematological parameters in our patient seemed to improve soon after treatment was initiated; however, none of the prior cases in the literature experienced any long-term hematological issues, suggesting that supportive management can be a reasonable alternative.